THE USE OF SHORT STORY TO INCREASE STUDENTS VOCABULARY (JoTELL : Journal of Teaching English, Linguistics, and Literature, 2022)
A short story is a story that is written shorter than a novel and longer than a fable Short stories focus on larger or smaller issues and focus on building strong feelings from the readers A short story tells about one aspect of a character s life This aspect of life can be an event a picture of a feeling or a simple action in the life of a character Short stories can also influence or even inspire readers Because it is no longer a taboo if short stories are widely used in the English learning process One of the important aspects in learning English is Vocabulary Teaching this aspect is neither easy nor difficult There are many things that teachers can use to improve vocabulary because vocabulary in the learning process needs to use appropriate techniques methods one of which can use short stories Therefore this study wanted to find out how the effect of short stories on increasing students vocabulary In the process this research uses a quantitative approach with a pre experimental design In this design the model is one group pre test and post test 20 students of class VIII A were taken as samples in this study to calculate the results of the student test the researcher used the mean score formula to analyze the data As the results the short story in the form of a storyline has a lot of vocabulary so that the students vocabulary is increasing this is proven by the significant difference between the students pre test and post test A short story is a story that is written shorter than a novel and longer than a fable Short stories focus on larger or smaller issues and focus on building strong feelings from the readers A short story tells about one aspect of a character s life This aspect of life can be an event a picture of a feeling or a simple action in the life of a character Short stories can also influence or even inspire readers Because it is no longer a taboo if short stories are widely used in the English learning process One of the important aspects in learning English is Vocabulary Teaching this aspect is neither easy nor difficult There are many things that teachers can use to improve vocabulary because vocabulary in the learning process needs to use appropriate techniques methods one of which can use short stories Therefore this study wanted to find out how the effect of short stories on increasing students vocabulary In the process this research uses a quantitative approach with a pre experimental design In this design the model is one group pre test and post test 20 students of class VIII A were taken as samples in this study to calculate the results of the student test the researcher used the mean score formula to analyze the data As the results the short story in the form of a storyline has a lot of vocabulary so that the students vocabulary is increasing this is proven by the significant difference between the students pre test and post test < p>